ANALISIS KUALITAS SOAL TES TERTULIS TINGKAT SMA OLIMPIADE BIOLOGI SE-RIAU DAN KEPULAUAN RIAU TAHUN 2018 BERDASARKAN RANAH KOGNITIF TAKSONOMI BLOOM - Miranti Miranti; Yuslim Fauziah; Darmawati Darmawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstact: This research was conducted to analyze item quality of written test for Senior High School in Biology Olimpiad at Riau dan Kepulauan Riau 2018. This research was carried out in October – November 2018. This research is a descriptive research, the data analyzed by quantitative method composed by difficult level, distinguishing power, fungtion of distractor, validity and reliability item and see domain cognitive by Taksonomi Bloom. Data source in this research are secondary data used participant answer sheet as the data. The result of quntitative method show that written test in the bad category based on clasification qualitative analyze, because only 15 items accepted, 76 items need to repaired and 9 items was rejected.Key Words: Analysis Item Quality, Wtitten Test, Taksonomi Bloom